Ledger of the East Tennessee Manufacturing Co. - East Tennessee Manufacturing Co.
Ledger (450 pages) with entries, chiefly 1850-1856, on debit and credit for various individuals and companies.
Iron manufacturing company in Chattanooga, Tenn.; later known as East Tennessee Iron Manufacturing Company.
Collection material in English.
Keywords: Iron industry and trade -- Tennessee -- Chattanooga; Chattanooga (Tenn.) -- Commerce